Arahan Pengembangan Lahan Potensial untuk Tambak Garam di Pesisir Kabupaten Rembang - Budi Prasetyo; Baba Barus; Darmawan (P4W LPPM IPB, 2022)
Rembang Regency is one of the national salt production centers that potentially can be increased its salt production. This study was aimed to guide potential land development for salt ponds on the Rembang Regency coast. The overlay method between land suitability maps for salt ponds, land use maps, and Regional Spatial Plan (RTRW) maps of Rembang Regency was be used to analyze potential areas for salt pond development. The results showed that the coastal area of Rembang Regency, which had a land suitability class of S1 was 10,325 hectares, a land with suitability class S2 area was 5,687 hectares, and land with suitability class S3 was 2,471 hectares, while the not suitable area for salt ponds (N) was 17,813 hectares. The total land available for the salt ponds development was 3,560 hectares. Based on the economic analysis results, it was known that the salt production business carried out on the land with suitability classes S1, S2, and S3 will get profit. Potentially land for development of salt ponds, which in line with the RTRW was 2,484 hectares. The utilization of Rembang Regency coastland for salt production enhancement was directed into three categories. The first was land that needed to be maintained its productivity covered an area of 1,366 hectares. The second was land that could be used for extensification covered an area of 931 hectares. The last was land that needed to be intensified covered an area of 187 hectares.